Risking difference : identification, race, and community in contemporary fiction and feminism - Wyatt, Jean (SUNY series in psychoanalysis and culture., 2004)
"Risking Differences revisions the dynamics of multicultural feminist community by exploring the ways that identification creates misrecognitions and misunderstandings between individuals and within communities. Drawing on Lacanian psychoanalysis, Jean Wyatt argues not only that individual psychic processes of identification influence social dynamics, but also that social discourses of race, class, and culture shape individual identifications. In addition to examining fictional narratives by Margaret Atwood, Angela Carter, Sandra Cisneros, Toni Morrison, and others, Wyatt also looks at nonfictional accounts of cross-race relations by white feminists and feminists of color."--Jacket